STRATEGI INTERNAL STORYTELLING DALAM MEMBANGUN MOTIVASI KERJA KARYAWAN PT. MEGA GREEN TECHNOLOGY - Irwan; Suparno, Antoni; Pratiwi, Leny (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Universal, 2022)
This study aims to determine the internal storytelling strategy to build employee motivation at PT. Mega Green Technology. This type of research is a qualitative paradigm and an ethnographic method. The data in this study were collected through interviews, observation, and documentation studies. The results of this study are that building employee motivation through internal storytelling can provide policies that are used to provide incentives, compensation, sense of responsibility, enthusiasm, and maintain internal company solidarity. Through an internal storytelling approach, it can reduce the gap between employees and leaders at work and produce better work performance to achieve company goals